Rate of return risk of Islamic bank : empirical evidence in Malaysia - Zairy Zainol (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
The study aims to measure the exposure of the Islamic banks in Malaysia to the rate of return risk. The study also analyses the impact of changes in the market interest rate to the profitability of Islamic banks. This study involves two major techniques; namely, Vector Autoregressive (VAR) approach by using aggregated data and gap analysis by using bank level data in order to provide empirical evidences on the exposure of the Islamic banks to the rate of return risk. With VAR approach, using the data covering the period from January 1997 to December 2013, the method of analysis included time series econometric techniques of unit root test, cointegration test, impulse response function (IRF) and variance decomposition (VDC).With the second approach, namely Gap analysis, it is a technique for the measurement of rate of return risk which is particularly aimed to analyse the rate of return risk at the Islamic banks individually in order to see the effect of changes in market interest rates to the profitability of the Islamic banks. The repricing gap approach is used to measure the effect of rate changes on the Islamic banks' profitability. The study finds that the Islamic banks are exposed to the rate of return risk and displaced commercial risk (DCR) from the result of Granger causality test and IRF in the VAR analysis. The results of Gap analysis implies that the Islamic banks would benefit from a fall in market interest rate whereby rate on liabilities decline faster than rate on assets. This will cause a wider spread of the rates and the Islamic banks stand to gain more profit from it. In addition, the profitability of the Islamic banks is vulnerable to an increase in market interest rate. The findings of this study have a major implication on the Islamic banks practice. The most important issue to address is the issue of sensitivity of Islamic banking products to the changes in the conventional banks' interest rate. The main reason of this issue is the practice of benchmarking the Islamic banks' rate of return against the conventional market interest rate. It is crucial that the concept of rate of return risk should be treated differently from the interest rate risk as this may lead to a problem of identification of rate of return risk in the Islamic banking system and also its impact. Moreover, this will cause a misconception of the Islamic banks mechanism of operation. In accepting major findings of this study, the policymakers should be aware of the fact that the Islamic banks are largely exposed to the rate of return risk. The results of this study have important implications to the Islamic banking system in Malaysia, particularly to ensure the healthy growth of these institutions. This can be done through a better risk management by using several ways of hedging the rate of return risk which could possibly exist in the Islamic banking system.